Philips: curling iron / Nur Anis Aisya Mohamad - Mohamad, Nur Anis Aisya (2022)
Philips is a global electronics industry leader that was established in 1891. The Netherlands' Royal Philips Electronics is a large corporation with a focus on health and education. Provide technical services and sell customer goods in three areas: fitness, lifestyle, and lighting. Philips is actively innovating and incorporating innovations and design strategies aimed at providing consumers with knowledge and delivering on the pledge of "meaning & simplicity." Furthermore, Philips' approach prioritizes sustainable sustainability. I’ve been given a task to make a case study to create my own product. As for the beginning I’m able to study about the company background and also analyze about the products that is manufactured by the company. By doing that, I’ve learned a lot about the strategy and how to manage the company. In this case study also I learned about how to analyze the product is by using SWOT analysis which are strength, weakness, opportunity and threats. By doing that, I am able to detect the problems and the solution. Thus I also can make a new improvement and add new features to my own product in future.